Effect of the standard operating procedure Box Method to increase self-confidence and basic nursing skills of nursing students during the COVID-19 pandemic - Wea, Lidwina Dewiyanti; Danal, Paskaliana Hilpriska; Ningsih, Oliva Suyen (Gaceta Médica de Caracas, 2022)
Introduction: Coronavirus Disease 2019 (COVID-19) pandemic develops an overwhelming new challenge not only to public health but also to nursing education and the workforce. Online methods brought difficulties to laboratory practice. Thus, this study aimed to identify the effect of using the nursing procedure box method as a remote and active learning method on nursing students’ basic nursing skills and self-confidence during a COVID-19 pandemic.